Democratic constitutional design and public policy : analysis and evidence - Congleton, Roger D.; Swedenborg, Birgitta, 1941-; Studieförbundet Näringsliv och samhälle. (Cambridge, Mass. : MIT Press, 2006)
Leading scholars in rational choice analysis present the public choice, new institutionalist, and new political economy perspectives on the political and economic effects of constitutional design and review the accumulating empirical evidence.
Introduction : rational choice politics and institutions / Roger D. Congleton and Birgitta Swedenborg -- Direct democracy : designing a living constitution / Bruno S. Frey and Alois Stutzer -- Constitutions and economic policy / Torsten Persson and Guido Tabellini -- Party-line voting and committee assignments in the German mixed-member system / Thomas Stratmann -- The effects of constitutions on coalition governments in parliamentary democracies / Daniel Diermeier, Hülya Eraslan, and Antonio Merlo -- On the merits of bicameral legislatures : intragovernmental bargaining and policy stability / Roger D. Congleton -- Bicameralism and political compromise in representative democracy / John Charles Bradbury and W. Mark Crain -- Federalism : a constitutional perspective / Dennis C. Mueller -- Common tax pool problems in federal systems / Brian Knight -- Judicial independence and economic Growth : some proposals regarding the judiciary / Lars P. Feld and Stefan Voigt -- Constitutions and prosperity : the impact of legal and economic institutions on the wealth of nations / Randall G. Holcombe, Robert A. Lawson, and James D. Gwartney -- Amendment procedures and constitutional stability / Bjørn Erik Rasch and Roger D. Congleton -- Designing constitutional stability / Barry R. Weingast.
Papers originally presented at a conference sponsored by the Center for Business and Policy Studies.
Includes bibliographical references and index.
Print version record.
English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Comparative government -- Congresses; Political science -- Decision making -- Congresses; Rational choice theory -- Congresses; Political planning -- Congresses; Policy sciences -- Congresses; Economic policy -- Congresses; Constitutional law; Institutions politiques comparées -- Congrès.; Politique -- Prise de décision -- Congrès.; Théorie des choix rationnels -- Congrès.; Politique publique -- Congrès.; Sciences de la politique -- Congrès.; Politique économique -- Congrès.; Droit constitutionnel; 89.35 democracy; POLITICAL SCIENCE -- Public Policy -- General; Comparative government; Constitutional law; Economic policy; Policy sciences; Political planning; Political science -- Decision making; Rational choice theory; Vergleichende politische Wissenschaft; Grondwetten; Politieke besluitvorming; Vergelijkende politicologie; OESO-landen.; Choix rationnels, Théorie des -- Congrès.; Politique publique -- Congrès.; Techniques de décision en politique -- Congrès.; Politique économique -- Congrès.; Droit constitutionnel; Comparative government -- Congresses; Political science -- Decision making -- Congresses; Rational choice theory -- Congresses; Political planning -- Congresses; Policy sciences -- Congresses; Economic policy -- Congresses; Constitutional law; proceedings (reports); Conference papers and proceedings; Congresses (form); Conference papers and proceedings; Actes de congrès.